2020
DOI: 10.1038/s41598-020-58465-x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell – Inner Plexiform Layer Damage in Diabetic Patients: 3-Year Prospective, Longitudinal, Observational Study

Abstract: Diabetes is expected to accelerate age-related ganglion cell-inner plexiform layer (GC-IPL) loss, but there is limited information on the rate of reduction in GC-IPL thicknesses. We aimed to evaluate the reduction rate of GC-IPL thickness in diabetic patients, and to compare the rates between patients without and with diabetic retinopathy (DR). We included 112 eyes of 112 patients with diabetes [49 eyes without DR (no-DR group) and 63 eyes with mild to moderate non-proliferative DR (NPDR group)] and 63 eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
(32 reference statements)
1
34
0
Order By: Relevance
“…Previous studies have reported GC-IPL damage in patients with T2DM [ 22 , 23 , 24 ]. Ng et al [ 22 ] reported that subjects with T2DM but without DR had an average GC-IPL thinning of 4.37 μm, compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported GC-IPL damage in patients with T2DM [ 22 , 23 , 24 ]. Ng et al [ 22 ] reported that subjects with T2DM but without DR had an average GC-IPL thinning of 4.37 μm, compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ng et al [ 22 ] reported that subjects with T2DM but without DR had an average GC-IPL thinning of 4.37 μm, compared to controls. Lim et al [ 23 ] found that the estimated reduction rate of the average GC-IPL thickness in T2DM patients without DR (−0.627 μm/year) was 2.26-fold faster than that in normal individuals (−0.277 μm/year). We obtained similar results: The GC-IPL was significantly thinner in T2DM patients than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Third, patients with comorbidities such as diabetes mellitus and hypertension were also included in the study. It has been reported that diabetes or hypertension affects GC-IPL and RNFL, and this change can occur even without retinopathy [21,22,51,52]. However, there were no statistically significant differences among the three groups concerning diabetes and hypertension, as presented in Table 1, so it is considered that the effect of diabetes and hypertension would be small.…”
Section: Plos Onementioning
confidence: 84%
“…Studies on GC-IPL thickness have reported observations of various ocular disorders, including glaucoma, neuro-ophthalmic diseases, and macular diseases [21][22][23][24]. Approximately half of the retinal ganglion cells are concentrated in the macula [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation